Using dried blood spot testing for diagnosing viral hepatitis. (12th November 2020) - Jack, Kathryn; Irving, William Lucien
Abstract : The target set by the World Health Organization to eliminate viral hepatitis as a public health problem by 2030 first requires methods of testing for hepatitis B and C virus that are acceptable to diverse populations. One such test is the dried blood spot sample method. This article explains what a dried blood spot sample is, how it is collected, and how it can help increase the viral hepatitis test uptake in prisons, drug and alcohol services, and other populations at risk of hepatitis B or C infection.